Effects of Varieties and Nitrogen Fertilizer on Yield and Yield Components of Maize on Farmers Field in Mid Altitude Areas of Western Ethiopia - Tolera Abera; Tolessa Debele; Dagne Wegary (International Journal of Agronomy)
Yield of maize hybrids could be low when grown below optimum management practices. Use of improved varieties and optimum nitrogen fertilizer application practices are unlocking the high yielding potential of hybrids maize. With these in view, a field experiment was executed on farmers’ field to determine the effect of varieties and nitrogen fertilizer rate on yield and yield components of maize in two cropping seasons. It is laid out with randomized complete block design in factorial arrangement with three replications. Five maize varieties (BH-540, BH-543, BH-661, BH-660, and BH-140) as main factor and two levels of nitrogen (55 and 110 Kg N ha−1) as subfactor were used with one maize variety (BH-543) without fertilizer as control. Leaf area and leaf area index of maize varieties were significantly affected by application of nitrogen fertilizer rates. Interaction of maize varieties with nitrogen fertilizer rates significantly affected all yield and yield components of maize. Application of half and full recommended nitrogen fertilizer produced mean grain yield advantages of 31 and 41% over control. Therefore, application of half and full recommended nitrogen fertilizer for improved maize varieties has significantly improved grain yield and recommended for maize production in midaltitude area of western Ethiopia.